2012
DOI: 10.1080/10874208.2012.705770
|View full text |Cite
|
Sign up to set email alerts
|

Application of Neurofeedback in General Neurology Practice

Abstract: Neurofeedback (NFB), also called EEG biofeedback, is infrequently applied in general neurology practice. Therefore, this study was conducted to evaluate the clinical usefulness of NFB in neurological settings. Over the period of approximately 15 months, 25 subsequent patients who were interested in NFB therapy and completed at least 20 sessions of NFB treatment were analyzed for potential clinical benefits. Patients' subjective responses were collected after NFB treatment to see if any improvement of symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Yet, the current QNF studies in the literature do report positive treatment outcomes. Moreover, while traditional and SCP NF mostly focus on ADHD symptoms, QNF studies report covering a wider range of symptoms, syndromes and disorders that include, behavior aspects, mood, cognitive dysfunction, epilepsy, head injuries, autism spectrum, migraines, learning disorders, schizophrenia, post-traumatic stress disorder, Down syndrome, and intellectual disability (Arns et al, 2012;Breteler et al, 2010;Coben & Myers, 2010;Huang-Storms, Bodenhamer-Davis, Davis, & Dunn, 2006;Koberda, Hillier, Jones, Moses, & Koberda 2012;Surmeli et al, 2012;Surmeli & Ertem, 2007, 2009Walker, 2009Walker, , 2010bWalker, , 2011Walker, , 2012bWalker, , 2013. This literature collection largely represents retrospective investigations from clinical settings.…”
Section: Qeeg-guided Nf (Qnf)mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the current QNF studies in the literature do report positive treatment outcomes. Moreover, while traditional and SCP NF mostly focus on ADHD symptoms, QNF studies report covering a wider range of symptoms, syndromes and disorders that include, behavior aspects, mood, cognitive dysfunction, epilepsy, head injuries, autism spectrum, migraines, learning disorders, schizophrenia, post-traumatic stress disorder, Down syndrome, and intellectual disability (Arns et al, 2012;Breteler et al, 2010;Coben & Myers, 2010;Huang-Storms, Bodenhamer-Davis, Davis, & Dunn, 2006;Koberda, Hillier, Jones, Moses, & Koberda 2012;Surmeli et al, 2012;Surmeli & Ertem, 2007, 2009Walker, 2009Walker, , 2010bWalker, , 2011Walker, , 2012bWalker, , 2013. This literature collection largely represents retrospective investigations from clinical settings.…”
Section: Qeeg-guided Nf (Qnf)mentioning
confidence: 99%
“…This allows for more neuroregulation and enhanced QEEG normalization. Consequently, in clinical reports of ZNF it is suggested that positive clinical outcomes can be achieved in an average of 10 to 20 sessions (Collura et al, 2010;Koberda et al, 2012b;Wigton, 2013 The available z-score metrics and multiple channels of the ZNF modalities greatly enhance NF specificity. With surface 4ZNF and 19ZNF, the dysregulated areas and rhythms can be isolated for normalization, and even more so with the Laplacian montage (Thatcher, 2013).…”
Section: Loreta Znf (Lznf)mentioning
confidence: 99%
“…The goal is to reinforce increased stability within the various aspects of the human attention network depending on the patient's symptoms. Figure 2 is a Talairach atlas representation of the Brodmann areas (nodes) and connections between Brodmann areas of the dorsal attention network that is used in LORETA Z score NFB (Koberda, 2011;Koberda, Hiller, et al, 2012;Thatcher, 2012Thatcher, , 2013. Figure 3 is a Talairach atlas representation of the Brodmann areas (nodes) and connections between Brod- Figure 2.…”
Section: Attention Networkmentioning
confidence: 99%
“…Surface Z scores improve specificity by isolating dysregulated locations and rhythms, especially when using the Laplacian transform and low-resolution electromagnetic tomography (LORETA) Z scores (i.e., real-time or ''live'' comparisons to a normative database). For example, LORETA Z score biofeedback also often produces results in one 20-min session because EEG source localization has accuracies similar to fMRI of about 1 cm to 3 cm and therefore is much more specific than is surface EEG (see Koberda, 2011;Koberda, Hiller, Jones, Moses, & Koberda, 2012;Thatcher, 2010Thatcher, , 2012Thatcher, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover the pre-post qEEG data analysis was limited in scope. Koberda, Hillier, Jones, Moses, and Koberda (2012) reported on the use of qNF in a clinical setting of a neurology private practice. All 25 participants were treated with at least 20 sessions of a single-channel traditional NF protocol, which was guided by qEEG data and symptoms, with a goal to improve symptoms and normalize the qEEG.…”
Section: Normalization Model Of Qnfmentioning
confidence: 99%